Geostrophic and ageostrophic circulation of a shallow anticyclonic eddy off Cape Bojador. Issue 2 (22nd February 2014) - Ruiz, Simón; Pelegrí, Josep L.; Emelianov, Mikhail; Pascual, Ananda; Mason, Evan
Abstract A shallow mesoscale anticyclonic eddy, observed south of the Canary Islands with satellite altimetry, has been intensively studied with multiparametric sampling. Hydrographic data from a CTD installed on an undulating Nu‐shuttle platform reveal the presence of a mesoscale anticyclonic eddy of ∼125 km diameter. The difference in sea level anomaly (SLA) between the interior and the edge of the eddy, as determined from altimetry, is ∼15 cm, which compares well with the maximum dynamic height differences as inferred using a very shallow reference level (130 m). Further, the associated surface geostrophic velocities, of about 35 cm s−1 in the northeast and southwest edges of the eddy, are in good agreement with direct velocity measurements from the ship. Deep rosette‐CTD casts confirm that the structure is a shallow eddy extending no deeper than 250 m before the fusion with another anticyclone. The SLA‐tendency (temporal rate of change of sea surface height) indicates a clear northwestward migration during the two first weeks of November 2008. Applying an eddy SSH‐based tracker, the eddy's velocity propagation is estimated as 4 km d−1. Use of the QG‐Omega equation diagnoses maximum downward/upward velocities of about ±2 m d−1. The instability of the Canary coastal jet appears to be the mechanism responsible for the generation of the shallow anticyclonic eddy.